A second species of Brasilotyphlus (Amphibia: Gymnophiona: Caeciliidae) from Brazilian Amazonia - Maciel, Adriano O.; Mott, Tami; Hoogmoed, Marinus S. (Zootaxa, 2009)
Brasilotyphlus is rediagnosed in light of the discovery of a second species of the genus, B. guarantanus sp. nov., in the municipality of Guarantã do Norte, state of Mato Grosso, Brazil. The new species differs from B. braziliensis mainly in annular counts, having 151–170 primaries and at most 2 secondaries (instead of 142–147 primaries and 23–36 secondaries).